Usefulness of chest CT scan for head and neck cancer. Issue 1 (February 2015) - Fukuhara, Takahiro; Fujiwara, Kazunori; Fujii, Taihei; Takeda, Kenichi; Matsuda, Eriko; Hasegawa, Kensaku; Nomura, Kenichi; Kitano, Hiroya
Abstract Objective Chest computed tomography (CT) is not performed routinely or worldwide as the initial diagnostic procedure for patients with head and neck cancer (HNC). The significance of the chest CT scan for HNC diagnosis has not been thoroughly defined. The present study reports findings in an effort to broaden the acceptance and application of CT for HNC. Methods Using medical records, we assessed initial chest CT scans of the patients with new-onset HNC between April 2004 and March 2010. The results were classified into three groups: nodules ≥1 cm, small nodules (<1 cm) that were indeterminate and normal lungs without nodules. Lung nodules that increased in size and/or number at follow-up were regarded as malignant. First, the sensitivity of X-ray and CT for detection of lung nodules in patients with HNC was compared. Second, the nodules were estimated to be malignant or not malignant by follow-up chest CT. Third, statistical analyses were performed to determine the association between variables and distant lung metastases in patients with head and neck squamous cell carcinoma. Results In total, 332 patients underwent a chest CT scan as part of the initial examination. Lung nodules were detected on the initial chest CT in 77 patients: in contrast, lung nodules were detected on the initial chest X-ray in only five patients. On initial chest CT scans, lung nodules ≥1 cm were observed in 10 patients, small solitary lung nodules were observed in 67 patients, and lungs without nodules were observed in 255 patients. Lung nodules were detected in 77 (23.2%) patients, 25 (32.5%) of whom had malignant lung nodules. Moreover, in 18/67 patients (26.9%), small lung nodules initially classified as indeterminate were determined as malignant at follow-up. However, 30/255 patients (11.8%) without nodules at initial diagnosis developed lung nodules at follow-up. T3 or T4 disease (P = 0.006), N2 or N3 disease (P < 0.001) and stage 3 or 4 disease (P = 0.001) individually and significantly correlated with the development of lung metastases. In addition, lung nodules in initial CT scans (P = 0.004) and other distant metastases (P < 0.001) were significant predictors for the development of lung metastases at follow-up. Conclusion Initial chest CT scan is recommended for patients with advanced HNC. Further, patients with advanced HNC with or without lung nodules, as detected on initial chest CT scans, should be followed up with additional scanning.